2016
DOI: 10.1515/aiht-2016-67-2837
|View full text |Cite
|
Sign up to set email alerts
|

Ectoine as a promising protective agent in humans and animals

Abstract: Ectoine is a compatible water molecule-binding solute (osmoprotectant) produced by several bacterial species in response to osmotic stress and unfavourable environmental conditions. This amino acid derivative can accumulate inside cells at high concentrations without interfering with natural processes and can protect the cell against radiation or osmotic stress. This brief review presents the current state of knowledge about the effects of ectoine on animals and focuses on its practical use for enzyme stabilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 55 publications
0
63
0
Order By: Relevance
“…Ectoine is a biocompatible naturally occurring solute present in extremophiles, which have the ability to survive in extreme environments, such as cold, hot, and salty conditions (Lippert & Galinski, 1992;Roberts, 2005). Ectoine is a low molecular weight permeating CPA and can accumulate intracellularly at high concentrations without interfering with normal cellular activities (Bownik & Stępniewska, 2016). Ectoine has been synthesized and used for decades in various biomedical applications (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectoine is a biocompatible naturally occurring solute present in extremophiles, which have the ability to survive in extreme environments, such as cold, hot, and salty conditions (Lippert & Galinski, 1992;Roberts, 2005). Ectoine is a low molecular weight permeating CPA and can accumulate intracellularly at high concentrations without interfering with normal cellular activities (Bownik & Stępniewska, 2016). Ectoine has been synthesized and used for decades in various biomedical applications (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Ectoine has been synthesized and used for decades in various biomedical applications (e.g. skin protection, anti-inflammatory drugs and neurodegenerative treatment) (Bownik & Stępniewska, 2016;Graf, Anzali, Buenger, Pfluecker, & Driller, 2008;Heinrich, Garbe, & Tronnier, 2007;Kanapathipillai, Lentzen, Sierks, & Park, 2005;Marini, Reinelt, Krutmann, & Bilstein, 2013;Sydlik et al, 2009). Although the protective mechanism of action has not been thoroughly investigated, it is probably associated with the preferential exclusion model of ectoine (Roberts, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Ectoine is an amino acid derivative produced mainly by aerobic, chemoheterotrophic and halophilic bacteria in response to osmotic stress and unfavorable environmental conditions. Ectoine is also known for its practical use for enzyme stabilization, human skin protection, anti-inflammatory treatment and inhibitory effects in neurodegenerative diseases (Bownik and St pniewska, 2016). It stabilizes cell membranes, enzymes, and nucleic acids at extreme temperatures or higher salt concentrations in some bacteria (Smiatek et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The other main component of the product studied, ectoin, is a natural compound produced by various bacterial species in response to osmotic pressure in extreme environmental conditions. It is a compatible solute which attaches itself to the water molecules and acts as an osmoprotectant [39]. Various studies have indicated that topical application of ectoin on human skin has beneficial effects.…”
Section: Discussionmentioning
confidence: 99%